Penerapan Konseling Kelompok Bagi Siswa yang Berperilaku Negatif dalam Penyesuaian Diri dengan Lingkungan Kelas 5 SDN 09 Ngringo, Jaten, Karanganyar - Laksana, Anggit, Nur Amalia, S.S., M. Teach (2017)
This research aims to knowing: (1) negative behavior which contained in grade V of SDN 09 Ngringo, Jaten, Karanganyar. (2) how to resolving negative behavior in grade V of SDN 09 Ngringo, Jaten, Karanganyar. (3) how to applying group counseling of students who behave negatively in grade V of SDN 09 Ngringo, Jaten, Karanganyar. (4) the results of the application of group counseling that has been applied of students who behave negatively and have difficulty adjusting themself to the environment in grade V of SDN 09 Ngringo, Jaten, Karanganyar. This study is a qualitative reseach with case study design. This research subject is class grade V of SDN 09 Ngringo, Jaten, Karanganyar. Data collection techniques using interviews, observations, and ocumentation. The validity of test data using triangulation techniques and triangulation methods. In this research, The data analysis techniques using data collection, data reduction, data display, conclusion drawing/verification. The recearcher collected data from events that actually happened in school through headmaster and teachers who apply group counseling, and students who behave negatively and have difficulty adjusting themself. Based on the results of data collection that happend at school, can be concluded that the group counseling which applying by teachers can help students who behave negative difficulty adjusting themself with their class environment.Key Words : group counseling, self djustment, negative behavior